Analisis Teknis dan Keekonomian Sistem Hibrida Pada Pelayanan Kelistrikan Pulau Rhun - Yogasara, Adams; Maulana, Rinaldi; Adi, Tri Wahyu (Politeknik Negeri Malang, 2024)
Indonesia, as the largest archipelagic country, faces significant challenges in providing consistent electricity to its numerous isolated microgrids, many of which rely on diesel generators. The limited operational hours of these systems hinder economic growth, especially in remote regions like Rhun Island. This research aimed to develop an optimized hybrid power system integrating photovoltaic (PV) panels and Battery Energy Storage Systems (BESS) to extend electricity availability and reduce reliance on fossil fuels. Using simulation tools such as PVsyst and HOMER Pro, the study evaluated various configurations to identify the most cost-efficient and sustainable solution. Additionally, Demand Side Management (DSM) strategies, including peak clipping and load shifting, were applied to further optimize the system's performance and reduce operational costs. The findings demonstrated that the hybrid system significantly decreased the Levelized Cost of Energy (LCOE) to 0.431/kWh compared to a diesel-only system. Furthermore, the renewable energy fraction increased to 81.7%, contributing to Indonesia's energy transition goals. This research offers a replicable model for other small islands, promoting sustainable energy solutions and supporting local economic development by ensuring a stable 24-hour power supply. The implications suggest that adopting hybrid systems with DSM can accelerate energy equity and environmental sustainability in remote areas.